PROFIL PEMECAHAN MASALAH BENTUK CERITA PADA MATERI PECAHAN SISWA KELAS VII SMP NEGERI MODEL TERPADU MADANI PALU: The Problem of Solving Story Problems on fraction Material In Grade VII Stundents At SMA Negeri Model Terpadu Madani Palu - Nurmaya; M, Bakri; Karniman, Tegoeh S. (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
This study aims to describe the problem solving of fractional. This type of research is descriptive using a qualitative approach. The subjects of this study were grade VII students of SMP Negeri Model Terpadu Madani Palu consisting of 3 students who were divided into 1 student with high mathematical abilities, 1 student with moderate mathematics ability, and 1 student with low mathematical abilities selected based on processing the final semester exam scores in odd semester 2021/2022. The results showed that students whit high math skills were able to solve problems well based on Polya’s problem solving steps, starting from the stage of understanding the problem, to the stage of re-examining the answers. Students who are mathematically capable are doing mathematical problem solving well at the stage of understanding the problem, the stage of making plans, but at the stage of implementing the plan students are wrong in changing the fraction division operation into the form of fraction multiplication operations, moderately capable subjects do not change the position of the numerator into the denominator and the denominator into the numerator which is the settlement area, the stage of re-checking the students answers only checks again by looking at the results of the answers. Students whit low math abilities have not done problem solving well, that is, they can only rewrite existing information without understanding the existing information, unable to make plans because they feel confused in thinking about plans that must be used to solve problems, cannot carry out problem solving plans. And can’t recheck the answer. This is because students cannot solve the given problem.